Effects of Teaching with Multimedia on Knowledge, Behavior in Face-down Positioning, and Satisfaction in Patients with Retina Diseases Undergoing Ophthalmic Gas Injection and in Face-down Position - Noyudom, Angun; Thongyost, Piyawadee (Nursing Research and Innovation Journal, 2024)
This two-group quasi-experimental study aimed to examine the effects of teaching with multimedia on knowledge, behavior in face-down positioning, and satisfaction with the teaching in patients with retina diseases undergoing ophthalmic gas injection and in face-down positions in a tertiary hospital.Purposive sampling with inclusion criteria was used to recruit 60 participants, divided into the experimental group (n = 30) and the control group (n = 30). The experimental group received teaching with multimedia plus usual care, while the control received only usual care. The research intervention used multimedia,namely caring for people with retinal disease afte rundergoing surgery with gas injection and in a face-down position. The instruments for data collection were the Demographic Data Form, the Knowledge Questionnaire, the Behavior in Face-Down Positioning after Surgery Questionnaire, and the Satisfaction with Multimedia Questionnaire. Data analyses were performed using descriptive statistics and the non-parametric Mann-Whitney U test. The findings revealed that at the pretest, the mean ranks of knowledge in the experiment and control groups were not significantly different. After the experimental group received multimedia teaching, the mean ranks of knowledge and postoperative behavior in the face-down position were significantly higher than those in the control group. The experimental group also had a significantly higher mean rank of knowledge after receiving multimedia teaching than the pretest. In addition, the participants in the experimental group were very satisfied with multimedia teaching. The study’s results demonstrate the effects of multimedia in providing knowledge and advising people with retinal disease undergoing gas injection to perform correctly.Therefore, teaching with multimedia is a method of choice to enhance patients’ knowledge by seeing pictures and hearing sound effects. This will allow a more accurate understanding of the contentand methods of performing face-down position and increase satisfaction with the service received. Keywords :Face down position,Multimedia,Ophthalmic gas injection,Retinal diseases